Diagnostic Biomarkers of Periodontitis and Early Detection of Periodontal Tissue - Hanan Selman Hessan Al Gebouri (American Journal of Biology and Natural Sciences, 2025)
This investigation delves into the complex interrelations between chronic systemic diseases—specifically diabetes mellitus and hypertension—and oral health disorders, namely periodontal disease and dental caries. The principal aim is to quantitatively assess the strength and statistical significance of these associations through rigorous analytical techniques. Utilizing data from the 2022–2024 cycles of the National Health and Nutrition Examination Survey (NHANES), the study analyzes a nationally representative cohort of 13,772 adults, encompassing detailed systemic and oral health variables. Oral health evaluation was conducted via clinical measures indicative of periodontitis and tooth decay, while systemic conditions were operationalized based on the diagnosis of diabetes and elevated blood pressure. Statistical assessment using Cramér’s V demonstrated moderate yet statistically significant correlations: periodontitis exhibited a moderate association with diabetes (Cramér’s V = 0.14), and dental caries showed a comparable association with hypertension (Cramér’s V = 0.12). These outcomes highlight the reciprocal dynamics linking oral and systemic health, suggesting that declining oral conditions may act as early indicators of broader systemic dysfunction. The findings advocate for the integration of oral health screening into chronic disease management protocols, especially for individuals at risk for or living with diabetes and hypertension.